Synthesis and tautomerism study of 6-benzoylmethyl-1,3,5-triazin-2,4-diamine - Sachdeva, N.; Dolzhenko, Anton; Chui, W. (Elsevier SAS, 2011)
From the reaction of biguanide with ethyl benzoylacetate, N-(6-oxo-4-phenyl-1,6-dihydropyrimidin-2-yl)guanidine and 6-benzoylmethyl-1,3,5-triazin-2,4-diamine were isolated.The structural evaluation of 6-benzoylmethyl-1,3,5-triazin-2,4-diamine was performed theoretically (DFT calculations) and experimentally (NMR spectroscopy and X-ray crystallography). The effects of solvents and temperature on keto-enol-enaminone tautomeric equilibrium were explored.